2011
DOI: 10.1002/jctb.2721
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and sensitive detection of SARS coronavirus nucleocapsid protein using quantum dots‐conjugated RNA aptamer on chip

Abstract: Here, a new quantum dots (QDs)-conjugated RNA aptamer with high sensitivity and rapidity is proposed for the detection of SARS-CoV N protein using an on chip system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
86
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(88 citation statements)
references
References 31 publications
0
86
0
Order By: Relevance
“…This miniaturization device based on optical QDs-RNA aptamer chip can detect SARS-CoV N protein at the concentrations of as low as 0.1 pg mL −1 . The suggested graphical SARS-CoV N protein method enjoys high sensitivity, accuracy, simplicity, and easy operation [ 170 ]. Table 2 presents a comparison between different methods for the detection of coronaviruses.…”
Section: Detection Methodsmentioning
confidence: 99%
“…This miniaturization device based on optical QDs-RNA aptamer chip can detect SARS-CoV N protein at the concentrations of as low as 0.1 pg mL −1 . The suggested graphical SARS-CoV N protein method enjoys high sensitivity, accuracy, simplicity, and easy operation [ 170 ]. Table 2 presents a comparison between different methods for the detection of coronaviruses.…”
Section: Detection Methodsmentioning
confidence: 99%
“…In another study, Roh and Jo designed a chip that detected SARS-CoV N proteins in only an hour with a detection limit of 0.1 pg/ml. The target proteins were immobilized on the chip via ProLinker™ capture probes, then quantum dots-labeled specific aptamers bound to the targets, and fluorescence intensity was evaluated using confocal microscopy [139]. In a recent study, Diao and colleagues proposed a fluorescent immunochromatographic strip assay that detected the N proteins in nasopharyngeal aspirate and urine samples of COVID-19 patients that took only 10 min with a sensitivity of 68-98%.…”
Section: Optical Biosensorsmentioning
confidence: 99%
“…This strategy offers many advantages; the DL-DNA can be used as both a structural scaffold and a probe while its detection mechanism relies on fluorescent color ratios instead of single color and can be easily adapted to a fluorescence detection system. Moreover, Roh et al reported a testing protocol using the system on a chip (SoC) technology whose detection mechanism is based on QDs-conjugated RNA aptamer [ 240 ]. The amine group of the RNA aptamer was covalently attached to the commercially available, fluorescent carboxyl terminated QDs605, usually made of a nanometer-scale CdSe core and ZnS shell to better control and modulate their optical response.…”
Section: Diagnostics and Biosensors For Covid-19mentioning
confidence: 99%